The gift of forgiveness - Stanley, Charles F. (Nashville, TN : Oliver Nelson, 1991)
Charles Stanley, one of the most influential spiritual leaders of our day, shares the key to personal and even world peace in this book. As Stanley points out that no sin is so shockingly evil it blocks God's forgiveness nor so trivial it negates the need for God's mercy, he shares the specifics of how to go about receiving and giving forgiveness. This book reflects the heart of Stanley's teaching ministry. In this markedly helpful book, Stanley addresses such questions as how to practice a life of forgiveness in all your relationships and how to make forgiveness an ongoing, practical experience in your life. - Publisher.
At head of title: Put the past behind you and give--
Originally published: Forgiveness. c1987.
Keywords: Forgiveness -- Religious aspects -- Christianity